Properties and Behavior of Sexual Life Stages Underlying Dinoflagellate HAB Events of Cyst-Producing Species That Disrupt Fisheries and Aquaculture - Agneta Persson; Barry C. Smith; Jennifer H. Alix; Gary H. Wikfors (Reviews in Fisheries Science & Aquaculture, 2024)

Dinoflagellate cell density limits explored using Scrippsiella lachrymosa cultured in flow-through cages - Barry C. Smith; Agneta Persson; Jennifer H. Alix (Journal of Applied Phycology, 2023)
Dinoflagellates constitute one of the most important groups of primary producers and micro-zooplankton on earth, common in both marine and freshwater environments. Despite their prominent position among phytoplankton, they are difficult to grow into dense cultures in the laboratory. This discrepancy between field and laboratory indicates serious limitations caused by the laboratory culturing conditions. A difficult to study but important factor is the constraints of enclosure in a limited volume of water. We conducted an experiment wherein the dinoflagellate Scrippsiella lachrymosa was grown in “flow cells” – 100 cm 3 cylindrical cages constructed from plankton net, inserted in larger volumes of growth medium, allowing an exchange of medium without dilution of the culture. Cell numbers far exceeding the normal for culturing of this species and dinoflagellates in general were attained, even though the experiment was terminated before cultures reached stationary phase. A cell number ten times higher than under regular batch culturing was achieved (up to 340,000 cells mL −1 ). Pattern formation was distinct in cultures when cells were plentiful and water movements caused cell accumulation, not dispersion. High cell density concurrent with access to new growth medium promoted induction of the sexual cell cycle. The results indicate serious limitations to growth set by enclosure in a limited water volume in laboratory experiments; thus, maximum growth rates of dinoflagellates in favourable field conditions may be vastly underestimated. Cell accumulation behavior of dinoflagellates during the sexual life cycle may together with physical transport by larger forces in nature explain sudden bloom occurrences.

Six-week follow-up after HIV-1 exposure: a position statement from the Public Health Agency of Sweden and the Swedish Reference Group for Antiviral Therapy - Hans Gaines; Jan Albert; Maria Axelsson; Torsten Berglund; Magnus Gisslén; Anders Sönnerborg; Anders Blaxhult; Gordana Bogdanovic; Maria Brytting; Christina Carlander; Leo Flamholc; Per Follin; et al. (Infectious Diseases, 2016)

Synchronization of encystment of Scrippsiella lachrymosa (Dinophyta) - Barry C. Smith; Agneta Persson (Journal of Applied Phycology, 2005)

Dinoflagellate cyst production in one-liter containers - Barry C. Smith; Agneta Persson (Journal of Applied Phycology, 2004)